Jean-Joseph Dubois-Foucou (1747-1830), Napoleon's Personal Dentist - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
Jean-Joseph Dubois-Foucou was born in Toulon on February 19,1748. He studied surgery in the hospital of the same town and in the "Hôpital de la Charité", the current University of Medicine. He graduated from surgery and was entitled master surgeon in 1766. On July 22, 1771, he officially became the member of the Royal Academy of Surgery in Paris. From this day, he practiced as a dental surgeon. As a matter of fact, his name was simply Dubois, but he added the name of Foucou, which was taken from one of his relatives, whowas an artist [1]. On July 22, 1775, Dubois-Foucou became a master in art andsurgical science when he upheld his thesis entitled: "De dentis vitiose positorum curatione" [2].